Methods for determining the risk of sewer failures - Kuliczkowska, Emilia; Wijas, Katarzyna (Instal, 2020)
The aim of the article was to present the selected method of risk assessment of sewer failures based on two parameters, i.e. probability of sewer failures and consequences of their occurrence. Factors that were taken into account and methods of determining both parameters were discussed. The result was to indicate differences in determining the risk level and some risk parameters in the presented methods. Determining the risk of sewer failure is a useful method in planning activities related to their trenchless rehabilitation, replacement or, for example, planning of cleaning the pipes from deposits.
Keywords: risk; likelihood of failure; consequence of failure; sewers